Advances in Bioremediation and Phytoremediation 2018
DOI: 10.5772/intechopen.70350
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Scale Biodegradation of Fuel Oil No. 6 in Contaminated Soils by Autochthonous Bacteria

Abstract: In order to evaluate the degradation of fuel oil no. 6 (FO6) in contaminated soil, laboratory-scale bioreactors were set up to study biostimulation, bioaugmentation, and natural attenuation processes. A solution of fertilizers was added in biostimulation and biouagmentation (0.03% N, 0.01% P). To the bioaugmentation process, an enrichment culture of indigenous hydrocarbon-degrading microorganisms was also added once a week. Total aerobic and hydrocarbon-degrading microorganisms were determined by plate count, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The consortium prepared from these genera is effective and degraded TPHs in a short incubation time. This is in agreement with the findings of Piñón-Castillo and colleagues [ 62 ], Goetz and coworkers [ 63 ], M’rassi and colleagues [ 64 ], and Ali and others [ 65 ], who reported that single strain Acinetobacter sp. A3 is capable of degrading 70% of TPH from crude oil-contaminated soils.…”
Section: Discussionsupporting
confidence: 93%
“…The consortium prepared from these genera is effective and degraded TPHs in a short incubation time. This is in agreement with the findings of Piñón-Castillo and colleagues [ 62 ], Goetz and coworkers [ 63 ], M’rassi and colleagues [ 64 ], and Ali and others [ 65 ], who reported that single strain Acinetobacter sp. A3 is capable of degrading 70% of TPH from crude oil-contaminated soils.…”
Section: Discussionsupporting
confidence: 93%
“…54 Since hexadecane is the primary energy source for the cells, it may be inferred that this increase in cell concentration was because of the increased consumption of hydrocarbons. 55,56 Based on our bacterial growth rate studies and MATH test, we can conclude that the growth rate and adsorption of A. borkumensis to the oil−water interface is enhanced by the addition of chitosan-coated lignin NPs. The chitosan-coated lignin NPs do attach to the bacterial surface as shown in our scanning electron microscope (SEM) image (Figures 4b and S4), thus further impacting the bacterial adhesion to the oil− water interface.…”
Section: Effect Of Ionic Strength On Np Stabilitymentioning
confidence: 80%
“…Thus, as the cells replicate in the presence of hydrocarbons, the alkB genes have a stronger expression and higher catabolic activity, resulting in increased degradation . Since hexadecane is the primary energy source for the cells, it may be inferred that this increase in cell concentration was because of the increased consumption of hydrocarbons. , …”
Section: Resultsmentioning
confidence: 99%